Mammalian Artificial Chromosomes Methods and Protocols - Sgaramella, Vittorio.; Sgaramella, Vittorio.; Eridani, Sandro.; Eridani, Sandro. (Methods in Molecular Biology,, 2004)
Assembly of the basic units of mammalian chromosomes into artificial constructs, and the reduction of their components to more manageable dimensions, has now become a reality. In Mammalian Artificial Chromosomes: Methods and Protocols, leading scientists in cell biology, genetics, cell culturing, and gene transfer present their most productive methods for the preparation, characterization, and use of artificial chromosomes. The authors cover all relevant areas of artificial chromosome research-from basic genetics to daring attempts at building new gene therapy tools-and describe possible applications in genetic manipulation requiring large portions of the genome. Each fully tested protocol is described in step-by-step detail and includes a background introduction outlining the principle behind the technique, reagent and equipment lists, and tips on troubleshooting and how to avoid pitfalls. Cutting-edge and much-needed, Mammalian Artificial Chromosomes: Methods and Protocols offers a timely collection of meticulous techniques that will help elucidate the mechanisms of nuclear duplication, allow the introduction of changes into the human genome, and revolutionize our understanding of how chromosomes work.